PENTINGNYA PENGORGANISASIAN DAN PERANAN ANALISIS JABATAN DALAM MENINGKATAN KUALITAS KERJA PADA CV. MANGGALA DESIGN AND FURNITURE - Ade Markus; Yuliansyah M. Diah; Muhammad Kosasih Zen (JEMBATAN, 2012)
ABSTRACT This research have purposed to know how organizing and applying of job analysis done by CV. Manggala Design and Furniture for increasing job quality to be effectively and efficient. Result of research show that organizing process covering indicators of coordination process, delegation of authority, and decentralization system of power that is not run carefully. Than the applying of job analysis that is not applies job specification for the recruitment of labor, lack of explanation of about job description so that employee has not owned clarity the things having to done, and division of duties which is not run at activity of its business. So employee quality of the labor who is covering time accuracy, result of job and complain minimalize received is not able to showed the optimal result. In order to increase quality of job at the CV. Manggala Design and Furniture, writer suggests that company is more improve or repairingly the coordination process, more multiplyingly the delegation frequency of authority, and focused at decentralization system of power only. Then clarifies intention from the job description, then give some training to improve specification of employee position who has not fulfilled qualification and improve division of duties employee as according their occupation. And changes complain to become guidance to employee who is having ugly quality, gives training that employee is more trains so the result of job can fulfill company claim, that is finally can effectively the order workmanship time.